The Factors Affecting Evolution of Cooperative Innovation Network on Platform: Based on the Prospect Theory - Yang LIU; Yanju XU (Communications of International Proceedings, 2020)
To explore evolutionary mechanism of cooperative innovation network on platform which collects users’ needs, this paper divides the technical ability of cooperators into the ability of identifying and implementing users’ needs. And based on the prospect theory, evolutionary game is adopted to analyze the cooperative behavior of finite rational participants. According to the topological structure of the cooperative network on platform built by core enterprise, this paper uses MATLAB to simulate on the BA scale-free network. It is found that the sensitivity degree of marginal diminishing of perceived gains or losses as well as the coefficient of loss avoidance affect the frequency of cooperation negatively. And there is optimal value of strengths to increase the gains of cooperative innovation and achieve win-win cooperation. It is difficult for the participants with high weaknesses to cooperate with others steadily.
Keywords: Cooperative innovation network on platform; Ability oriented to users’ needs; Evolutionary games; BA scale-free network; Prospect theory.